2016
DOI: 10.1038/srep36706
|View full text |Cite
|
Sign up to set email alerts
|

Facile Growth of High-Yield Gold Nanobipyramids Induced by Chloroplatinic Acid for High Refractive Index Sensing Properties

Abstract: Au nanobipyramids (NBPs) have attracted great attention because of their unique localized surface plasmon resonance properties. However, the current growth methods always have low yield or suffer tedious process. Developing new ways to direct synthesis of high-yield Au NBPs using common agents is therefore desirable. Here, we employed chloroplatinic acid as the key shape-directing agent for the first time to grow Au NBPs using a modified seed-mediated method at room temperature. H2PtCl6 was added both during t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
34
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 28 publications
3
34
0
Order By: Relevance
“…Colloidal AuNPs were synthesized using the seed-mediated method, slightly modified from the literature reported one (Fang et al, 2016). Briefly, 150 µL of 0.01 M HAuCl 4 .xH 2 O and 100 µL of 0.01 M H 2 PtCl 6 .xH 2 O were added into 9.75 mL of 0.1 M CTAB solution followed by the drop by drop addition of 900 µL of ice-cold (4˚C) freshly prepared 0.01 M of NaBH 4 under constant magnetic stirring at room temperature.…”
Section: Synthesis Of Aunps and Ligand Exchange Process (Figure 1 Stmentioning
confidence: 99%
“…Colloidal AuNPs were synthesized using the seed-mediated method, slightly modified from the literature reported one (Fang et al, 2016). Briefly, 150 µL of 0.01 M HAuCl 4 .xH 2 O and 100 µL of 0.01 M H 2 PtCl 6 .xH 2 O were added into 9.75 mL of 0.1 M CTAB solution followed by the drop by drop addition of 900 µL of ice-cold (4˚C) freshly prepared 0.01 M of NaBH 4 under constant magnetic stirring at room temperature.…”
Section: Synthesis Of Aunps and Ligand Exchange Process (Figure 1 Stmentioning
confidence: 99%
“…The high amount of energy required for pyrolysis and the inherent imperfection of attrition methods do not solve the limitations of top-down approaches. Thus, bottom-up approaches have been widely explored to produce AuNPs with a diverse range of sizes and shapes, such as spheres [9,32], rods [33,34], cubes [35], prisms [36,37], stars [38], cages [39], polygons [40] and many others [41,42] (Fig. 2).…”
Section: Introductionmentioning
confidence: 99%
“…Copyright 2011 The Royal Society of Chemistry; c prisms [37]. Copyright 2015 The Royal Society of Chemistry; d bipyramids [42].…”
Section: Introductionmentioning
confidence: 99%
“…35,36,45 Very recently, several groups demonstrated that the optimized synthesis of Au seeds allows for the direct preparation of high-quality Au NBs without the use of shape-selective precipitation. 33,48,49 However, for other metals, the syntheses of NBs have been rarely reported. As described above, Pd-based nanostructures are potential catalysts for many organic reactions and fuel cells, [10][11][12][13][14][15][16][17][18] and therefore, it is worth developing methods that can be used to prepare Pd NBs, and explore their catalytic performance.…”
Section: 33-46mentioning
confidence: 99%